The Potential Toxicity of Animal Oils to Pathogenic Fungi Nila Fish (Oreochromis niloticus) - Katili, Deidy Y; Singkoh, Marina Flora Oktavine; Rondonuwu, Frans Bernhard; Umboh, Stella Deiby; Langoy , Marnix L D; Montong, Vivi B (JURNAL BIOS LOGOS, 2025)
Nila is a type of freshwater fish that has high economic value, as a source of animal protein for the community, and is an important commodity in the freshwater fish business. Nila is also one of the main commodities that contributes to the increase in aquaculture production. Nila farming often faces the problem of declining yields due to diseases. One of the diseases that is very detrimental to freshwater fish is diseases caused by fungi. The purpose of this study is to test the toxicity of animal oil in inhibiting the growth of Nila pathogenic fungi. Isolation of pathogenic fungi in fish is carried out by cutting the infected parts (scales, fins, and gills) with a size of about 1x1cm. After pure culture is carried out on each pathogenic fungus, then macroscopic and microscopic identification is carried out. Animal oil (lard oil) is taken in the market that is already available. Animal oil is made in four concentration series, namely 25ppm, 50ppm, 75ppm, and 100ppm and control (0ppm). The toxicity test was carried out in vitro using the toxic bait method, which was carried out by growing Nila pathogenic fungi inoculum on PDA media that had been mixed with animal oil. The results of animal fungicide toxicity testing in 5 treatments (A= control – E= 100 ppm) obtained the diameter of pathogenic fungal colonies (5 pathogenic fungi) ranging from 2.88 cm – 6.82 cm. Animal oil fungicides can affect pathogenic fungi in fish, this can be seen in pathogenic fungi Aspergillus sp. which has a relative resistance of 49% (100 ppm), the category is quite influential with a colony diameter of 3.5 cm and in the pathogenic fungus Mucor sp. With a relative resistance of 56% (100 ppm), the category is quite influential with a colony diameter of 2.88 cm.